Metal wheel tyres from the Ancient Near East and Central Asia - Crouwel, J. H. 1943- (2014)
Important developments in wheel construction can be observed in Iraq and other parts of the Near East during the later third and earlier second millennium B.C. One such innovation is the appearance of clamped-on tyres made in bronze or copper segments. Recent, spectacular finds from Turkmenistan in Central Asia extend the already wide distribution of tyres of this distinctive form. They also shed light on the kinds of wheel and vehicle on which such metal tyres were used.
Keywords: Wheels; Tires; Automobiles; Stelae; Terracotta; Hobnails; Cemeteries; Axles; Sumer